Effect of crank length on joint-specific power during maximal cycling - Barratt, P. R.; Korff, T.; Elmer, S. J.; Martin, J. C. (Medicine & Science in Sports & Exercise, 2011)
Previous investigators have suggested that crank length has little effect on overall short-term maximal cycling power once the effects of pedal speed and pedaling rate are accounted for. Although overall maximal power may be unaffected by crank length, it is possible that similar overall power might be produced with different combinations of joint-specific powers. Knowing the effects of crank length on joint-specific power production during maximal cycling may have practical implications with respect to avoiding or delaying fatigue during high-intensity exercise.